The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acsomega.3c02072
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Simultaneous Lighting–Imaging System

Abstract: In a III-nitride multiple quantum well (MQW) diode biased with a forward voltage, electrons recombine with holes inside the MQW region to emit light; meanwhile, the MQW diode utilizes the photoelectric effect to sense light when higher-energy photons hit the device to displace electrons in the diode. Both the injected electrons and the liberated electrons are gathered inside the diode, thereby giving rise to a simultaneous emission-detection phenomenon. The 4 × 4 MQW diodes could translate optical signals into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Fu et al used a similar MQW diode structure to demonstrate simultaneous emitting and detecting properties. 177 A 4 × 4 array of these devices was demonstrated to work as a potential smart screen that can be used as a display and camera at the same time. The MQW diode also showed promising results regarding refresh rates which meet the requirements of most screen resolutions, and has also shown that it can detect a 1 Mbps signal.…”
Section: Integrationmentioning
confidence: 99%
“…Fu et al used a similar MQW diode structure to demonstrate simultaneous emitting and detecting properties. 177 A 4 × 4 array of these devices was demonstrated to work as a potential smart screen that can be used as a display and camera at the same time. The MQW diode also showed promising results regarding refresh rates which meet the requirements of most screen resolutions, and has also shown that it can detect a 1 Mbps signal.…”
Section: Integrationmentioning
confidence: 99%